Contactless automated manipulation of mesoscale objects using opto-fluidic actuation and visual servoing - Vela, Emir (2014)
This work describes an automated opto-fluidic system for parallel non-contact manipulation of microcomponents. The strong dynamics of laser-driven thermocapillary flows were used to drag microcomponents at high speeds. High-speed flows allowed to manipulate micro-objects in a parallel manner only using a single laser and a mirror scanner. An automated process was implemented using visual servoing with a high-speed camera in order to achieve accurately parallel manipulation. Automated manipulation of two glass beads of 30 up to 300 μm in diameter moving in parallel at speeds in the range of mm/s was demonstrated.